Revisão bibliográfica sobre processo da aquisição do inglês como segunda língua na primeira infância - Kozikoski, Jóice Aparecida (2020)
This work investigates the acquisition process of English as a second language in early childhood. Highlighting the relationship between cognitive development, mother tongue development, and factors like the age, family and social context in second language acquisition. The study in second language acquisition involving children has been getting stronger due to several reasons, including the increasing number of bilingual schools and the high exposure of the children to English language through the internet, cartoons and similar sources. The study was carried out by means of bibliographic research about children‟s development, language development, second and first language acquisition, bilingual studies. The selection of readings started from broad themes to specifics ones, using articles and books related the topics above. The main authors reviewed for the study were Jean Piaget (1896 – 1980), Lev Vygotsky (2007), Marcello Marcelino (2009), Eric Lennenberg (1969), Ellen Bialystok (1988, 2008, 2012), among others. Study results suggest that age is a factor that facilitates second language acquisition in early childhood. However, family, social and cultural interaction that offer children contact with a second language is another necessary condition for language acquisition. As regards bilingualism, it is possible to notice code-switching is recurring phenomenon and it does not indicate a cognitive disadvantage. Similarly to second language acquisition, interaction in cultural, social and family circles are indispensable for bilingual development.